CinemaAfrica 2025/26: A Conversation with ... Kofi Owusu-Afriyie (Cinema Africa 2025/26, 2026)
In this conversation, Adebanjo Baderin sits down with Ghanaian producer Kofi Owusu-Afriyie to talk about his work and his participation in the Cinema Africa Bayreuth Film Festival. They discuss Owusu-Afriyie’s journey in film, including his role in bringing contemporary African stories to international audiences, and his experience presenting The Fisherman at the 17th edition of Cinema Africa. The festival, held at Cineplex Bayreuth from January 25–28, showcases diverse African cinema and fosters cultural exchange through screenings and filmmaker discussions.